Research Trends on Small-Sided Games in Soccer: A Bibliometric Analysis (Universitas Pendidikan Indonesia, 2025)
A valid, credible, and comprehensive literature meta-study determines the level of accuracy in diagnosing previous research findings. It determines the development of more meaningful and useful future research. The purpose of this study was to examine the development of research articles on small-sided games in soccer. This study is quantitative research with bibliometric study method. Data were collected using the Publish or Perish application applying keywords